Perwira Industries Sdn. Bhd. : precast concrete piles / Darus Mohd Fadzli... [et al.] - Mohd Fadzli, Darus; Mohamad, Mohd Khairil Anuar; Hamid, Masmunir; Mohd Din, Azrul; Ahmad Suhaimi, Ahmad Ridzuan (2002)
Malaysia is the one of the top develop country in the world. Therefore, all Malaysian people have to take chances by involved in the economy. They also have to increase their effort to develop their own business. Furthermore, this can introduce our country in the world. Our business will be operating in Jitra and the size or market is around Kedah and Perlis. This is because demand for precast concrete is more at this time. That's why we must have more company to produce this precast concrete. Our company has to make decision to piles one of the precast concrete product. Our operation will start on 18 January 2003. We must analyze and identify our risk before we want to involve in the business Our market size is around Kedah and Perlis. This is because these two states not have much supplier for precast concrete and in the process to grow up. We also want to be a bumiputera company that provides a precast product. We hope our mission wills success and we used all the chances that come to achieve in this business